2013
DOI: 10.3390/coatings3030166
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation Studies of the Structure and Properties of As-Deposited and Annealed Pulsed Magnetron Sputtered Titania Coatings

Abstract: Titanium dioxide thin films are durable, chemically stable, have a high refractive index and good electro/photochemical proprieties. Consequently, they are widely used as anti-reflective layers in optical devices and large area glazing products, dielectric layers in microelectronic devices and photo catalytic layers in self-cleaning surfaces. Titania coatings may have amorphous or crystalline structures, where three crystalline phases of TiO 2 can be obtained: anatase, rutile and brookite, although the latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…As mentioned above, the as-deposited coatings were assumed to be amorphous on the basis of analysis by XRD and Raman spectroscopy. This concurs with previous work, which showed that for pure titania coatings, strongly crystalline anatase structures formed for coatings annealed at 400 °C and that this structure persisted up to 600 °C before evidence of rutile was observed [50]. For doped titania coatings, the dopant element has an important influence on structural formation during the annealing of these coatings.…”
Section: Resultssupporting
confidence: 92%
“…As mentioned above, the as-deposited coatings were assumed to be amorphous on the basis of analysis by XRD and Raman spectroscopy. This concurs with previous work, which showed that for pure titania coatings, strongly crystalline anatase structures formed for coatings annealed at 400 °C and that this structure persisted up to 600 °C before evidence of rutile was observed [50]. For doped titania coatings, the dopant element has an important influence on structural formation during the annealing of these coatings.…”
Section: Resultssupporting
confidence: 92%
“…Raman spectroscopy which yields matching information with FTIR spectroscopy is used to identify molecular structures by their vibrational, rotational, and other low‐frequency modes. Raman analysis gives information about the nature of the bonds in a chemical structure and the position, shape, and intensity of the Raman peaks are related to sub‐stoichiometric defects, quantum confinement effects, crystal sizes, nanocrystallinity, and large interfacial areas …”
Section: Resultsmentioning
confidence: 99%
“…This exciting and rich set of material properties has made TiO 2 a valuable candidate for applications in many fields, as well as for fundamental science investigations. To date, the market demand on TiO 2 -based devices for photocatalysis [1][2][3][4], sensors [5,6], optical reflective coatings for highly innovative 2 of 18 applications [7,8] (innovative mirrors for gravitational wave interferometers, among the others [9][10][11][12]), solar cells [13][14][15], metal insulator semiconductor industry [16], self-cleaning application [17][18][19], water purification processes [20], has been systematically growing, especially for thin films and nanostructures. In addition, a constant effort has been made in setting up reliable computational techniques, mainly based on density functional theory (DFT), to predict and describe the properties of TiO 2 , not only in its crystalline forms, but also in the amorphous phase, as well as to simulate the amorphous to crystalline phase transition [21][22][23].…”
Section: Introductionmentioning
confidence: 99%